2020
DOI: 10.1103/physrevb.102.184508
|View full text |Cite
|
Sign up to set email alerts
|

Local thermal fluctuations in current-carrying superconducting nanowires

Abstract: We analyze the effect of different types of fluctuations in internal electron energy on the rates of dark and photon counts in straight current-carrying superconducting nanowires. Dark counts appear due to thermal fluctuations in statistically independent cells with the effective size of the order of the coherence length; each count corresponds to an escape from the equilibrium state through an appropriate saddle point. For photon counts, spectral broadening of the deterministic cutoff in the spectra of the de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Given a uniform distribution of absorption sites over the strip, the degree of smearing of the detection cutoff scales with the standard deviation in the statistical distribution of such non-uniformities. Recent studies of the count statistics and the PCR spectra in straight nanostrips without bends have shown that the impact of Fano fluctuations and the degree of geometric non-uniformity in NbN nanostrips are not sufficient to explain the smearing of the red boundary in the DE [39]. The authors furthermore found that local thermal fluctuations and the static non-uniformities in the superconducting energy gap should produce measurable smearing of the spectral cutoff.…”
Section: Detection Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Given a uniform distribution of absorption sites over the strip, the degree of smearing of the detection cutoff scales with the standard deviation in the statistical distribution of such non-uniformities. Recent studies of the count statistics and the PCR spectra in straight nanostrips without bends have shown that the impact of Fano fluctuations and the degree of geometric non-uniformity in NbN nanostrips are not sufficient to explain the smearing of the red boundary in the DE [39]. The authors furthermore found that local thermal fluctuations and the static non-uniformities in the superconducting energy gap should produce measurable smearing of the spectral cutoff.…”
Section: Detection Scenariomentioning
confidence: 99%
“…Alternatively, in extremely narrow nanostrips, a dark count may appear as the consequence of multiple simultaneous phase-slip events [41]. It has been also shown that both current and temperature dependences of dark counts in straight strips without bends can be described by the Langer-Ambegaokar-McCamber-Halperin model [42,43] generalized for two dimensions with the effective size of the fluctuating volume of the order of a few superconducting coherence lengths [39].…”
Section: Detection Scenariomentioning
confidence: 99%
“…On the other hand, the study of the charge carriers fluctuation processes provides a deeper comprehension of the physical mechanisms in a large variety of systems, as observed in iron-based superconducting materials 13 , 14 and nanowires 15 , and in granular aluminum oxide superconducting thin films 16 , 17 and nanostructures 18 , as well as in superconducting qubits 19 . Fluctuation phenomena may influence the main figures of merit of the SNSPD devices, such as jitter 20 , dark counts 21 , 22 , and latching 23 . Moreover, their study may help revealing details about the detection mechanism in single photon detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the operation of a photon detector is intrinsically based on nonequilibrium dynamics 25 , which may be strongly affected by statistical fluctuations phenomena. For instance, the interaction between the quasi-particles (qp) and the substrate via phonon escape in the last stage of the detection process, is an example of normal state processes where fluctuations may play an important role 21 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the study of the charge carriers fluctuation processes provide a deeper comprehension of the physical mechanisms in a large variety of systems, as observed in iron-based superconducting materials [13,14] and nanowires [15], and in granular aluminum oxide superconducting thin films [16,17] and nanostructures [18], as well as in superconducting qubits [19]. Fluctuation phenomena may influence the main figures of merit of the SNSPD devices, such as jitter [20], dark counts [21,22], and latching [23].…”
mentioning
confidence: 99%